Personal Reflections on Sakha Matriculture: Transcript - Vinokurova, Aina (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
In this recorded interview, Aina Vinokurova shares her personal reflections about being a Sakha woman and Sakha (Yakuts) matriculture. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Sakha (Yakuts) Matriculture